2016
DOI: 10.1001/jama.2016.12399
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for Vitiligo

Abstract: Vitiligo is chronic idiopathic disorder of skin pigmentation that plays havocs with the social livings of patients. Its major symptom is the occurrence of white patches/lesions on human skin. It affects 1-2 % of general population. A 15 years juvenile patient was affected by generalized Vitiligo with no familial history of the ailment. The patient was asked to take two table spoonful of honey per oral mixed with one cup of boiled milk of cow early in the morning daily. White de-pigmented skin was observed to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 5 publications
1
47
0
Order By: Relevance
“…The topical corticosteroid used for vitiligo treatment in the Dr. Soetomo Hospital was clobetasol propionate (a highly potent corticosteroid) 0.05%. This is in accordance with Ezzedine, Whitton, & Pinart (2016), who showed that potent corticosteroids were effective at treating localized and stable lesions.…”
Section: Indications For Nb-uvb Radiation and Topical Corticosteroid supporting
confidence: 92%
“…The topical corticosteroid used for vitiligo treatment in the Dr. Soetomo Hospital was clobetasol propionate (a highly potent corticosteroid) 0.05%. This is in accordance with Ezzedine, Whitton, & Pinart (2016), who showed that potent corticosteroids were effective at treating localized and stable lesions.…”
Section: Indications For Nb-uvb Radiation and Topical Corticosteroid supporting
confidence: 92%
“…Treatment for at least 2-3 months is needed to determine efficacy of treatment. UV light-based therapy is the most common treatment for vitiligo and, when combined with an additional therapy, is associated with an improved outcome [165].…”
Section: Managementmentioning
confidence: 99%
“…18,19 In a meta-analysis study, vitiligo was associated with vitamin D deficiency and topical vitamin D analogues and phototherapy have been shown to be effective in the treatment. 20,21 Alopecia areata is a T-cell mediated disease targeting the hair follicle.…”
Section: Discussionmentioning
confidence: 99%